2022
DOI: 10.1088/2399-6528/ac8785
|View full text |Cite
|
Sign up to set email alerts
|

Performance of dye-sensitized solar cells extracted dye from wood apple leaves

Abstract: In this work, wood apple leaves dye has been extracted, characterized, and examined as a potential photosensitizer for dye-sensitized solar cells (DSSCs). The dye was extracted in an ethanolic medium from the fresh wood apple leaves and characterized using thin-layer chromatography (TLC), ultraviolet-visible (UV-Vis), and Fourier transform infrared (FTIR) spectroscopy. The current density-voltage (J-V) characteristics measurements were performed on the two assembled DSSCs for 1- 22 days using fresh and seven d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
(89 reference statements)
1
3
0
Order By: Relevance
“…Where A absorbance, ε is the molar absorption coefficient, C is the molar concentration, and l is the optical path length [21]. Broadening of the bands in the range 635-674 nm was observed for higher concentrations, indicating chlorophyll-chlorophyll interactions, as has been observed in similar studies [19]. The bandgap energy of the material in the solid-state form is the difference between the conduction and valence band energies.…”
Section: Optical Properties Of Pumpkin Dye Extractssupporting
confidence: 53%
See 3 more Smart Citations
“…Where A absorbance, ε is the molar absorption coefficient, C is the molar concentration, and l is the optical path length [21]. Broadening of the bands in the range 635-674 nm was observed for higher concentrations, indicating chlorophyll-chlorophyll interactions, as has been observed in similar studies [19]. The bandgap energy of the material in the solid-state form is the difference between the conduction and valence band energies.…”
Section: Optical Properties Of Pumpkin Dye Extractssupporting
confidence: 53%
“…A peak at approximately 333 nm represents the existence of C=O or C=C functional groups that are responsible for the n-π * electronic transition that can initiate electrical circuits in DSSCs and can facilitate their adsorption onto TiO 2 surfaces [17,18]. Two prominent absorption bands in the blue visible (450-500 nm) and red visible (635-674 nm) ranges have been observed in other related studies and are attributed to the presence of chlorophyll b and chlorophyll a [19,20]. From figure 1(a), it is observed that the absorbance increases with dye concentration and can follow the Beer-Lambert Law represented by equation (1).…”
Section: Optical Properties Of Pumpkin Dye Extractsmentioning
confidence: 56%
See 2 more Smart Citations